Capacitación científica y actividades de la red. Brasil - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1986)
A total of 1407 advanced breeding lines entered Brazil in 1985. After inspection for the presence of unknown diseases, the advanced lines were field-evaluated for their adaptation to different environments. A list is given of the 10 best red/purple, black, cream, and red advanced lines and common and local checks tested in preliminary yield trials over the different locations. Also, a total of 1009 crosses were made at CIAT and F2 and F3 populations were shipped to Brazil in Dec. 1985. These crosses were made to incorporate resistance to drought, anthracnose, angular leaf spot, rust, and common bacterial blight. (CIAT)